2017
DOI: 10.1111/coa.12913
|View full text |Cite
|
Sign up to set email alerts
|

Vocal palsy increases the risk of lower respiratory tract infection in low‐risk, low‐morbidity patients undergoing thyroidectomy for benign disease: A big data analysis

Abstract: There is a significant association between post-thyroidectomy vocal palsy and long-term risks of hospital readmission, dysphagia, hospitalisation for lower respiratory tract infection, and gastrostomy/tracheostomy tube placement. This adds weight to the need, from a thyroid surgical perspective, to undertake universal post-thyroidectomy laryngeal surveillance as a minimum standard of care, with a focus on post-operative dysphagia and aspiration, and from a medical/respiratory perspective, to initiate investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
(90 reference statements)
0
31
1
1
Order By: Relevance
“…Injury to the recurrent laryngeal nerve (RLN) is one of the most dreaded complications in endocrine neck surgery. Injury can present as paralytic dysphonia, dysphagia, paroxysmal coughing, aspiration, limited social functioning, or acute airway obstruction and is associated with significant morbidity . In addition, RLN injury has been ranked among the leading reasons for malpractice lawsuits …”
Section: Introductionmentioning
confidence: 99%
“…Injury to the recurrent laryngeal nerve (RLN) is one of the most dreaded complications in endocrine neck surgery. Injury can present as paralytic dysphonia, dysphagia, paroxysmal coughing, aspiration, limited social functioning, or acute airway obstruction and is associated with significant morbidity . In addition, RLN injury has been ranked among the leading reasons for malpractice lawsuits …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the postoperative management can be adapted to an observed LOS, i.e., a meticulous breathing therapy to prevent pneumonia can be exerted. VCP was demonstrated to significantly influence the risk of hospital readmission, dysphagia, hospitalization for lower respiratory tract infection, and gastrostomy/tracheostomy tube placement [5]. Since conventional continuous IONM with direct vagal stimulation would require an additional port during robot-assisted or minimally invasive esophagectomy, the non-invasive nerve monitoring making use of the laryngeal adductor reflex, as described by Sinclair et al [34], is of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the mechanism of injury, VCP can be transient or permanent. VCP is associated with a postoperatively elevated risk of aspiration pneumonia and voice impairment [4,5]. Furthermore, bilateral VCP can lead to a mechanically based respiratory insufficiency, which potentially requires tracheotomy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…VFP that occurs in the immediate postoperative setting has clinical implications regardless of prognosis for recovery. 8 Impaired glottic closure caused by unilateral VFP in the immediate postoperative period can lead to significant functional deficits including communication impairment, dyspnea, and dysphagia. Bilateral VFP in the immediate postoperative period can lead to airway compromise and the need for emergent intervention ( Table 2).…”
Section: Statement 1: Immediate Vocal Fold Paralysismentioning
confidence: 99%
“…Studies also revealed that long-term mortality from VFP lessened with early diagnosis and treatment, but never returned to a normal baseline in matched pair analysis. 8 Recognizing VFP as a significant complication, requiring early diagnosis and intervention, is vital to minimizing associated morbidity and maintaining an optimal patient-doctor relationship. There is significant psychosocial morbidity with VFP that can contribute to frustration, isolation, fear, and altered self-identity for patients.…”
Section: Introductionmentioning
confidence: 99%